South Florida Tropical Fruit Grower Perspectives: Water Conservation Management Practices - Kati W. Migliaccio; Jonathan H. Crane; Edward Evans; Bruce Schaffer; Yuncong Li; Rafael Muñoz-Carpena (EDIS)
Revised! ABE368, a 6-page fact sheet by Kati W. Migliaccio, Jonathan H. Crane, Edward Evans, Bruce Schaffer, Yuncong Li, and Rafael Muñoz-Carpena, presents results of fruit grower responses from a survey designed to assess changing views of agricultural producers in Miami-Dade county from 2006 to 2009 regarding water quantity and quality management practices — methods, demographics, water quality and quantity opinions concerning lifestyle, agriculture, and best management practices (BMPs). Includes references. Published by the UF Department of Agricultural and Biological Engineering, November 2009.